Approximation of transient redox boundary conditions: its application to numerical analysis of iron plume migration near landfills - Chung, Jaeshik; Chung, Jae H.; Townsend, Timothy G. (SPRINGER, 2019)
An efficient scheme is presented that attempts to implement the moving boundary conditions in a two-dimensional finite difference analysis model that simulates reductive dissolution and subsequent precipitation of iron species in surficial aquifer exposed to time-dependent redox boundary conditions near landfills. A mathematical and numerical model for simulating the vertical flux of oxygen through the variably saturated vadose zone and resulting hydrochemical response of groundwater system is developed and subsequently used to study dissolved iron plume migration phenomena from substrates beneath landfills. The proposed modeling scheme of the boundary condition is then applied to the groundwater system near an in-service landfill site located in state of Florida to produce an approximate solution to highly nonlinear boundary-value problems in hydrochemical systems subjected to various site geometries and soil conditions. As a result of the 12 years of consecutive runs with annually updated boundary conditions, a steady-state distribution of iron concentration is obtained and well compared with historical in situ data of groundwater iron concentrations depending on the desired degrees of accuracy.
Keywords: HYDRODYNAMIC DISPERSION; SOLUTE TRANSPORT; GROUNDWATER; AQUIFER; SOIL; SORPTION; GEOCHEMISTRY; PARAMETERS; IMPACTS; MEDIA